1.25–2.5 Gb/s Simple Nyquist Transmitters for Coherent UDWDM-PON with Enhanced Spectral Efficiency. Issue 4 (4th July 2018) - Velásquez, J. Camilo; Tabares, Jeison; Cano, Iván N.; Prat, Josep
ABSTRACT: We present a coherent ultra-dense wavelength division multiplexing passive optical network (UDWDM-PON) with enhanced spectral efficiency. The benefit of using Gaussian or Nyquist pulse-shaping filters at the transmitter is evaluated through numerical simulations and experiments. The transmitters consist of directly phase modulated distributed feedback (DFB) lasers through beat signals whose duty-cycle and amplitude are digitally adjusted. The results show that transmitting a Nyquist-shaped signal achieves a 25% spectral saving allowing to place 2.5 Gb/s/user data in 6.25 GHz channels. Furthermore, the proposed transmitter tolerates differential link-losses of 15 dB at Rx sensitivity of ‒44 dBm at BER=10 ‒3 with intradyne detection.